A Push for Professional Development Innovators. (3rd September 2019) - Colburn, Jeffrey; Stephenson, Rachyl; Keating, Xiaofen
Abstract : The challenges regarding professional development (PD) for physical education teachers (PETs) have been widely documented. PD for PETs is often ineffective, disconnected from PETs interests and needs, and sometimes provided in content other than physical education (PE). Several researchers have studied PD for PETs and have identified several problems as well as suggested effective ways to move forward including various PD components that have shown promise. Unfortunately, even with these suggestions, PD for PETs remains problematic because it has been suggested that there is a gap between the current PD practices for PETs and effective PD. Therefore, this article continues the ongoing inquiry about the most effective ways to help PETs participate in career-long professional learning and growth by providing an overarching framework and set of key factors to assist PETs to lead their own PD in an era of widespread cultural and educational change across the world.